Permanent Education in Health: A Documentary Investigation on the Eastern Region of the City of São Paulo (Global Journal of Human-Social Science, 2023)
The present article aims to present the data recorded in the Permanent Education Municipal Plans Planos Municipais de Educa o Permanente PLAMEP regarding the educational activities offered to professionals working in Primary Care services under the Regional Health Coordination Office - East in the period from 2017 to 2020 The article seeks to highlight the quantity and type of areas themes proposed of actions offered and their periodicity Some important issues have emerged in this survey among them the prevalence of more vertical methods deployed in educational actions such as training and courses along with a prevalent monthly periodicity of such activities differences in the amount of educational actions proposed in the course of the period considered a diversity of actions not circumscribed to the areas previously defined in the survey the lack of filling in some information such as executing area and periodicity in the first years of the PLAMEP implementation the lack of standardization and uniformity in the spreadsheets of 2017 and 2018 and an improvement in the organization of data between 2019 and 2020
Keywords: permanent education; primary care; health professionals; documentary survey